Decoloniality as Methodological Praxis - Eric J. Hunting (Adult Education Research Conference, 2022)
This paper examines decoloniality and ethnographic research using Maria Lugones' theoretical conceptualization of motion and stasis. In doing so, this supports developing a decolonial praxis-oriented toward culturally responsive research.
Keywords: methodology; decoloniality; ethnography